Influence of pneumatic transportation on the stability of monoclonal antibodies - Coliat, Pierre; Erb, Stéphane; Diemer, Hélène; Karouby, Dan; Martin, Tristan; Banerjee, Mainak; Zhu, Chen; Demarchi, Martin; Cianférani, Sarah; Detappe, Alexandre; Pivot, Xavier (Scientific reports, 2023)
Pneumatic transportation systems (PTS) were recently proposed as a method to carry ready-for-injection diluted monoclonal antibodies (mAbs) from the pharmacy to the bedside of patients. This method reduces transportation time and improves the efficiency of drug distribution process. However, mAbs are highly sensitive molecules for which subtle alterations may lead to deleterious clinical effects. These alterations can be caused by various external factors such as temperature, pH, pressure, and mechanical forces that may occur during transportation. Hence, it is essential to ensure that the mAbs transported by PTS remain stable and active throughout the transportation process. This study aims to determine the safety profile of PTS to transport 11 routinely used mAbs in a clinical setting through assessment of critical quality attributes (CQA) and orthogonal analysis. Hence, we performed aggregation/degradation profiling, post-translational modifications identification using complementary mass spectrometry-based methods, along with visible and subvisible particle formation determination by light absorbance and light obscuration analysis. Altogether, these results highlight that PTS can be safely used for this purpose when air is removed from the bags during preparation.